ANALISIS TERJADINYA MISFILE REKAM MEDIS TERHADAP PENYIMPANAN DI PUSKESMAS MUKAPAYUNG - Aisah Nuraeni (Jurnal Infokes, 2023)
The purpose of this study is to find out how misfiles that occur in medical records are related to storage at the Mukapayung Health Center. The research was conducted using a qualitative descriptive method, namely analyzing and describing the data and explaining in full the results obtained regarding the occurrence of misfiles. The results showed that there were errors in filling out medical records because of the educational level of the 5 officers, only 2 (40%) had medical records, 3 (60%) did not have medical records. Medical record training of the 5 officers who received training, only 2 (40%) and 3 (60%) did not receive training. Based on the research results in the first quarter of 2023, out of 50 samples of medical record files, 19(38%) files were lost, 36(56%) files were not lost, on February 17 (34%). missed files, 33(66%) missed files, on March 14(28%) missed files 36(56%) missed files. Medical record officers 2 PNS medical record staff and 3 honorary no medical record staff. Elements of the SOP method regarding the management of medical records already exist but are incomplete and there is no specific SOP regarding the storage and return of medical record data. Suggestion Conduct regular training for staff on proper filing procedures and the importance of maintaining accurate medical files. This will improve staff understanding and reduce the possibility of misfiles.Keywords: Misfile,Medical Record,Storage.